Utilizing Strategic Management Accounting Techniques in Iranian Firms - Seyedeh Ameneh Mirbagheri Roodbari; Gholamreza Kordestani (Environmental Energy and Economic Research, 2020)
The main objective of this article is to describe and explain the utilization of Strategic Management Accounting Techniques (SMATs) in Iranian various firms. For this, a survey was carried out using questionnaires provided for the seventy-five Chief Executive Officers in productive and services firms. Data gathered from respondents about the usage rate of SMATs based on the five-point Likert scale. The findings show that the usage rate of SMATs is different in the strategic management of quality, business, market, and competitors. The results suggest that all approximately major of SMATs has used in the different firms, while the strategic tools such as market segment analysis, product profitability analysis, competitors’ analysis, customers’ profitability analysis, R&D and MRP and a few other techniques are widely known among firms. Also, the use of these tools and techniques are not the same among the firms operating in various industries and having different size and ownership. As a result, there were identified hidden reserves for wider dissemination of Strategic management accounting in practice. The research disclosed that strategic management accounting could be assessed company-wide, seeking to find an optimal configuration of the local management accounting system from Technical - managerial view.